KEADILAN ORGANISASI, KEPUASAN KERJA DAN PEMBERDAYAAN PEGAWAI YANG BERDAMPAK PADA KOMITMEN ORGANISASI - Fajar, Catur Martian; Rohendi, A. (IKONOMIKA, 2016)
Abstact-This study aims to determine the effect of organizational justice, job satisfaction, and empowerment of employees on organizational commitment On Education and Training Center Geology Bandung. The independent variable in this study is organizational justice, job satisfaction, and employee empowerment, as well as the dependent variable in this study is the organization's commitment method used in this research is descriptive verification with quantitative approach. Based on a statistical test can know that justice organization partially significant effect on organizational commitment. Based on a statistical test can know that variable of organizational justice, job satisfaction, and employee empowerment partially or simultaneously has a significant influence on organizational commitment. Based on the research results in improving organizational commitment, the Center for Education and Training Geological need to determine human resource planning strategy through organizational justice, job satisfaction, and employee empowerment.